Analkarzinom - Schulte, Nadine; Hofheinz, Ralf-Dieter (Der Onkologe, 2012)
Metastasized, local recurrent and non-resectable R0 anal carcinomas represent a therapeutic challenge because due to the low incidence of the tumor and the rarity of metastases following adequate radiochemotherapy, only very little data on medication therapy is available. From the older literature it can be derived that protocols with cisplatin/5-fluorourcil represent a reasonable primary therapy when metastases are present and can therefore be recommended. Using this therapy the mean survival is approximately 12-15 months. Furthermore, several case reports have documented that the group of molecular targeted therapies, especially with the epidermal growth factor receptor (EGFR) antibody cetuximab, has shown promising results. However, in the opinion of the authors a KRAS analysis should be initiated before induction of therapy. Attempts at primary or secondary resection of metastases by a possible R0 resection seem to be justified.